2017
DOI: 10.1111/fwb.12901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total dissolved solids on growth and mortality predict distributions of stream macroinvertebrates

Abstract: Summary Spatial distributions of many freshwater invertebrates are associated with the concentration of total dissolved solids (TDS) in streams (usually measured as specific electrical conductivity – EC). These patterns are presumably caused by taxon‐specific effects of TDS on the maintenance of ion and water balance, which is energetically expensive and thus could affect fitness. However, no studies have assessed if TDS‐related effects on fitness metrics, such as growth and survival, are predictive of distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 43 publications
3
37
0
2
Order By: Relevance
“…The future EC predicted in 2100 indicates losses of an additional 42% of this habitat, for a total loss of 69% of low EC habitat in which most taxa evolved. Loss of these low EC habitats would stress the biota in these systems adapted to low salinity environments [32,33], leading to taxa losses, shifts in composition and potentially changes in ecosystem processes [34].…”
Section: Discussionmentioning
confidence: 99%
“…The future EC predicted in 2100 indicates losses of an additional 42% of this habitat, for a total loss of 69% of low EC habitat in which most taxa evolved. Loss of these low EC habitats would stress the biota in these systems adapted to low salinity environments [32,33], leading to taxa losses, shifts in composition and potentially changes in ecosystem processes [34].…”
Section: Discussionmentioning
confidence: 99%
“…[]). Even relatively small changes in suspended sediment concentrations (SSC) can adversely affect aquatic biodiversity, especially affecting species with a narrow range of suspended sediment tolerance [ Olson and Hawkins , ]. For this reason, regulatory agencies have been using criteria to regulate sediments in inland water bodies often using turbidity as a surrogate for suspended sediments [ US Environmental Protection Agency ( EPA ), ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been suggested that the ability of some invertebrates to tolerate dilute water may allow them to inhabit a wide range of water salinity. However, physiological mechanisms to overcome low water salinity likely evolve at the expense of other traits that are beneficial at higher water salinity conditions [11, 26,27]. According to this hypothesis, we expect that organisms adapted to low salinity will maintain similar levels of survival through different experimental salinity levels, but will reduce their behavioral performance at higher salinity as an expression of the costs of low-salinity adaptation.…”
Section: Introductionmentioning
confidence: 99%